A Human Lung-Associated Streptomyces sp. TR1341 Produces Various Secondary Metabolites Responsible for Virulence, Cytotoxicity and Modulation of Immune Response - Herbrík, Andrej; Corretto, Erika; Chroňáková, Alica; Langhansová, Helena; Petrásková, Petra; Hrdý, Jiří; Čihák, Matouš; Krištůfek, Václav; Bobek, Jan; Petříček, Miroslav; Petříčková, Kateřina (Frontiers in Microbiology, 2020)
Streptomycetes, typical soil dwellers, can be detected as common colonizers of human bodies, especially the skin, the respiratory tract, the guts and the genital tract using molecular techniques. However, their clinical manifestations and isolations are rare. Recently they were discussed as possible “coaches” of the human immune system in connection with certain immune disorders and cancer. This work aimed for the characterization and evaluation of genetic adaptations of a human-associated strain Streptomyces sp. TR1341. The strain was isolated from sputum of a senior male patient with a history of lung and kidney TB, recurrent respiratory infections and COPD. It manifested remarkably broad biological activities (antibacterial, antifungal, beta-hemolytic, etc.). We found that, by producing specific secondary metabolites, it is able to modulate host immune responses and the niche itself, which increase its chances for long-term survival in the human tissue. The work shows possible adaptations or predispositions of formerly soil microorganism to survive in human tissue successfully. The strain produces two structural groups of cytotoxic compounds: 28-carbon cytolytic polyenes of the filipin type and actinomycin X2. Additionally, we summarize and present data about streptomycete-related human infections known so far.